Kirurško zdravljenje malignih epitelijskih tumorjev kože - Ahčan, Uroš (Radiology and oncology (Ljubljana), 1999)
Skin tumors are considered one of the most common neoplasms in humans. They can be benign, premalignant or malignant. Most often they occur on photodamaged skin in ederly population. The most important malignant tumors are the basal and the squamous cell carcinoma. if untreated, they cause large local tissue destruction. Early and accurate diagnosis and early surgical removal of tumor togeher with histological verification of th etumor and surgical margins ensure efficient treatment and good aesthetic results. Skin tumors should always be excised to healthy margins (tumor-free tissue). When there is no tenson int ewoound primary wound closure shoould be performed by interrupted sutures or continuous intradermal suture. When the skin defect after tumor excision is small split or full thickness skin grafts or local rotation and transposition flaps are used for coverage. Large defect are covered by distant or free flaps. The flap transfer usually leaves a secondarydefect which is closed either by direct suture or covered by a skin graft.
Keywords: Carcinoma; kirurško zdravljenje; kožne spremembe; kožni rak; Skin neoplasms; Surgery